Eight-week virtual reality training improves lower extremity muscle strength but not balance in adolescents with intellectual disability: A randomized controlled trial - Wang, Shuhan; Yu, Hao; Lu, Zhaoxia; Wang, Jiangna (Frontiers in Physiology, 2022)
Purpose: This study aims to assess the effects of 8-week virtual reality (VR) training on balance and lower extremity muscle strength in adolescents with intellectual disability (ID). Methods: Thirty adolescents with ID were randomly divided into the VR group and control group. The participants in the VR group and the control group received the VR training and the physical education (PE) course, respectively, for 8 weeks. The Berg Balance Scale (BBS), Timed Up and Go (TUG) test and lower extremity muscle strength were measured before and after the training. Results: The between-group results showed that the participants in the VR group increased the muscle strength of hip flexors (P<0.001), hip extensors (P=0.002), hip abductors (P<0.001), knee flexors (P<0.001), knee extensors (P=0.002) and ankle plantar flexors (P=0.042) significantly after training, compared to the control group. However, no significant improvement was found in the BBS and TUG scores between the VR group and control group after training (P>0.05). The within-group results showed that the strength of all the muscle groups significantly increased after training in the VR group (P < 0.05) compared to the baseline. However, no significant difference was found in the muscle strength in the control group before and after training. The within-group BBS and TUG scores showed no significant improvements in both groups. Conclusion: VR training intervention might be effective in improving the lower extremity muscle strength, but no significant improvement was found on balance ability in adolescents with ID.